Sexual practices and reproductive choices for sero different to HIV couples - Dalapria, Taís Renata; Ximenes Neto, Francisco R.G. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: until recently, questions directed to sero-difference to HIV were not given their due importance; to this extremely delicate and socially fearful matter, which could potentially interfere or cause problems in the married life of couples. Objective: to identify the sexual practice of sero different to HIV heterosexual couples and to identify the aspirations related to family growth and reproductive choices, as well as characterizing their social-demographic profile. Methods: the study was held in the period from October to September 2003, in Sobral Ceará, with six sero different to HIV heterosexual couples. Results: it is noted that, all of the couples have children or are expecting; none of the individuals is aware of artificialin semination and two declare a wish to have more children. As for sexual practice, four couples only practice vaginal sex and two practice oral, analand vaginal sex. Conclusion: science has dedicated it self little to investigate sexual practices amongst sero different to HIV heterosexual couplesand their aspirations related to family development; maybe through lack of interest from health professionals, who in their great majority are overbur-dened or dispersed from this reality or maybe through lack of knowledge on this theme.